2009
DOI: 10.1111/j.1365-2052.2008.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymorphisms in the bovine β‐lactoglobulin gene and their effects on β‐lactoglobulin protein concentration in milk

Abstract: The aim of our study was to detect new polymorphisms in the bovine beta-lactoglobulin (beta-LG) gene with significant effects on beta-LG protein concentration. Genomic DNA samples from 22 proven bulls were screened for polymorphisms in the coding and promoter regions of the beta-LG gene. In total, 50 polymorphisms were detected. Two single nucleotide polymorphisms (SNPs) (g.1772G>A and g.3054C>T) lead to amino acid changes and are the causal genetic polymorphisms of beta-LG protein variants A and B. Forty-two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 19 publications
4
58
2
Order By: Relevance
“…The number of polymorphisms identified in our breeds showed high variability of the BLG promoter region as reported by Sardina et al [37] in goat and by Ganai et al [45] in cattle. Valle del Belice and Comisana breeds had all point mutations (36 SNPs and the deletion) in common, whereas the Pinzirita breed presented 34 SNPs and the deletion, and [30].…”
Section: Identification Of Polymorphisms and Genetic Diversity Indexessupporting
confidence: 83%
“…The number of polymorphisms identified in our breeds showed high variability of the BLG promoter region as reported by Sardina et al [37] in goat and by Ganai et al [45] in cattle. Valle del Belice and Comisana breeds had all point mutations (36 SNPs and the deletion) in common, whereas the Pinzirita breed presented 34 SNPs and the deletion, and [30].…”
Section: Identification Of Polymorphisms and Genetic Diversity Indexessupporting
confidence: 83%
“…In a study by Ganai et al (2009), SNP within the PAEP gene were identified in relation to β-LG concentration. In that study, the A variant of PAEP was shown to have a significant negative effect on relative concentration of β-LG, whereas other studies have shown a negative effect of the B variant on β-LG concentration (Allmere et al, 1998b;Hallén et al, 2008).…”
Section: Major Qtl On Chromosomementioning
confidence: 99%
“…PRLR is one of the main proteins of bovine milk (Ganai et al, 2009 showed the highest milk yield, while GG genotype cows showed the highest fat content (Shi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%